2019
DOI: 10.1016/j.jdent.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Array analysis for T-cell associated cytokines in gingival crevicular fluid: Identifying altered profiles associated with periodontal disease status

Abstract: Changes made as a result of publishing processes such as copy-editing, formatting and page numbers may not be reflected in this version. For the definitive version of this publication, please refer to the published source. You are advised to consult the publisher's version if you wish to cite this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(65 reference statements)
2
5
0
Order By: Relevance
“…In contrast, IFNγ is a signature cytokine of Th1-mediated immunity. 24 Our findings are in agreement with previous literature suggesting increased presence of IFNγ in periodontally involved sites. 17,25 Moreover, our findings suggest that intrabony defect sites, similarly to periodontal sites with no defect configuration specification, cannot be solely characterized as Th2dominated lesions, but instead an interplay between Th1-and Th2mediated immunity takes place.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, IFNγ is a signature cytokine of Th1-mediated immunity. 24 Our findings are in agreement with previous literature suggesting increased presence of IFNγ in periodontally involved sites. 17,25 Moreover, our findings suggest that intrabony defect sites, similarly to periodontal sites with no defect configuration specification, cannot be solely characterized as Th2dominated lesions, but instead an interplay between Th1-and Th2mediated immunity takes place.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the significantly increased GCF levels of IL‐6 reported here for intrabony defect sites, compared with periodontally healthy sites, support the transition of adaptive immunity toward Th2 predominance in intrabony lesions. In contrast, IFN‐γ is a signature cytokine of Th1‐mediated immunity 24 . Our findings are in agreement with previous literature suggesting increased presence of IFN‐γ in periodontally involved sites 17,25 .…”
Section: Discussionsupporting
confidence: 93%
“…Compared with that mediated by Tregs, the Th17 cell‐mediated immune response occupies a dominant position in periodontitis 15,119 . Therefore, the decreased Th17/Treg cell ratio reflects the degree of pathological bone resorption in periodontitis 30,120 …”
Section: Th17/treg Imbalance and Periodontal Bone Resorptionmentioning
confidence: 99%
“…In contrast to the above reports, the proportion of Foxp3 + CD25 + Tregs was lower in active periodontal lesions than in healthy gingival tissues, while the level of RANKL protein in periodontal tissue homogenates was negatively correlated with that of IL‐10 derived from Tregs but positively correlated with IL‐1β level 44 . Consistent with these observations, TGF‐β1 and IL‐10 mRNA levels were much lower in active as compared with inactive periodontal lesions, whereas Foxp3, T‐box expressed in T cells (T‐bet), RANKL, IL‐17, IL‐1β, and IFN‐γ levels showed the opposite trend 45,46 . Another study reported that the abundance of Tregs in the spleen was markedly reduced along with TGF‐β1 and IL‐10 mRNA levels in the gingival tissue of mice with experimental periodontitis induced by P. gingivalis 47 .…”
Section: Phenotypes and Roles Of Tregs In Periodontitismentioning
confidence: 47%